The effect of lime and mineral fertilizers on agrochemical characteristics of soil and productivity of birdsfoot trefoil and timothy grass mixture - A. P. Kislitsyna; V. A. Figurin (Аграрная наука Евро-Северо-Востока, 2021)
The article presents the results of three-year (2017-2019) field studies on changes in agrochemical characteristics of soil and formation of productivity of birdsfoot trefoil and timothy grass mixture in dependence of the liming (hydrolytic acidity 0.25) and application of mineral fertilizers, phosphorite meal in particular. The soil is sod-podzolic, medium loamy, strongly acidic, with intermediate concentration of mobile phosphorous and metabolizable potassium, humus content is 1.9 %, and mobile aluminum – from 4.27 to 5.24 mg/kg of soil. It has been established that application of finely ground lime at a dose of 3 tons per hectare prior to sowing of birdsfoot trefoil and timothy grass mixture decreased soil acidity in the layer of 0-10 cm from 4.2 to 5.6 pH units by next autumn. Application of phosphorite meal (1t/ha) led to an increase in the concentration of mobile phosphorous in the layer of 0-10 cm by 135-163 %. The highest productivity of birdsfoot trefoil and timothy mixture during 3 years was obtained by means of combined application of lime and mineral fertilizers, and for 3 years on the average the yield of metabolic energy exceeded 50 GJ/ha, which is over 35 % higher than in the control variant without fertilizers. The use of mineral fertilizers increased grass mixture productivity only during the first two years. The applied dosage of phosphorite meal (1t/ha) promoted the increase in grass productivity on strongly acidic soil only in the year of sowing. Additional treatment with ammonium nitrate (N30) together with phosphorous and potassium fertilizers (Р60К60), as well as potassium chloride (К60) with phosphorite meal did not result in significant rise in metabolizable energy yield.